sebuah PENGARUH SENAM KAKI DIABETES TERHADAP CAPILLARY REFILL TIME PADA KLIEN DIABETES MELLITUS DI PUSKESMAS DINOYO MALANG - Taufan Arif (Poltekkes Kemenkes Malang, 2018)
Introduce: Complications of DM can be short and long term. Long-term complications such as macroangiopathy damage that can cause peripheral vascular disease was decreased blood and leg circulation, and endothelial damage to blood vessels. The aim was to explain the influence of diabetic foot exercise on changes capillary refill time. Methods: The study was Quasy-experimental pre-post test design. The population were 30 respondents divided into treatment and control group. Data analysis using wilcoxon sign ranked test for 2 paired samples, and mann whitney test for 2 free samples. Result: The result of mann-whitney pre test test p value is 01287 while mann-whitney post test p value is 0.022. The results of the pre-post test of the treatment group using wilcoxon signed ranked p is 0.025 while the pre-post test of the control group using wilcoxon signed ranked p is 0.157. The results was influence of diabetes foot exercises on capillary refill time. Discuss: diabetes foot exercises performed at least 3 times a week within 4 weeks can improves Nitric Oxode Syntesis and arterial vasodilation so that it affects the peripheral microvascular signed CRT less than 2 sec. Hopefully there is diabetic foot gymnastics booklet to establish new clients. Keyword: Diabetes mellitus, Diabetes Foot Exercises, Capillary Refill Time